Carrier confinement for mobility enhancement in dual-gate organic thin-film transistors - Yu Shan; Zean Guo; Yuan Kai; Ke Hu; Jiawei Wang (Results in Physics, 2023)
Mobility of charge carriers in organic thin-film transistors (OTFTs) is one of the most important parameters, which is affected by the disorders in the semiconducting films. In general, realization of higher carrier concentration facilitates improved charge transport against these disorders. Here, we demonstrate in amorphous indacenodithiophen-co-benzothiadia (IDT-BT) based dual-gate organic thin-film transistors (DG-OTFTs) that the mobility can be robustly increased from 0.8 to 1.37 cm2 V−1 s−1, when voltage biases of opposite signs (negative one accumulate holes, positive one deplete holes) are applied on the dual independent gate electrodes. In details, the positive bias can confine the spatial distribution of the accumulated carriers near the negatively biased gate, leading to a higher effective carrier concentration with higher mobility. In addition, the interface confinement effect of carriers was further verified by two-dimensional numerical simulation, and calculations based on the variable range hopping method were performed to accurately reproduce the experimentally observed charge transport behavior in DG-OTFTs.